Local development through social and territorial innovation: An exploratory case study - Susana Bernardino (CIRIEC-España, Revista de Economía Pública, Social y Cooperativa, 2017)
This investigation aims to examine innovation in a selected successful Portuguese social ven- ture (The Cooperative Terra Chã) and to analyse the extent to which innovative social ventures are able to con- tribute to local development. Specifically, the paper highlights the activities developed by the social organization in response to the needs of particular (micro) segments of society and illustrates which key factors triggered the success of the examined social initiative. A case study methodology is used to describe the distinctive characte- ristics and strategies pursued by the managers of the social venture and to establish the links between the oppor- tunities for social innovation and the territory. The data collected for the study were triangulated from desk research and from in-depth semi-structured interviews conducted with privileged actors. The results show that social innovation is a viable strategy to revitalize the region’s socio-economic tissue, through the creation of new economic activities and consequently local employment that are based on the villa- ge’s traditional activities. This strategy seeks to achieve sustainable economic growth and well-being for the peo- ple of the region. However, to be successful, the strategy demands a deep knowledge of existing social problems as well as the availability of endogenous local resources and capabilities for use by social entrepreneurs. In this context, social innovation should be a participatory process, in which different entities and the beneficiaries of social programs were active players.